2016
DOI: 10.1308/205016816819304231
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Root Canal Infections

Abstract: Inflammatory reaction in the periapical tissues is induced by microbial infection in the root canal system. The aim of root canal treatment is to preserve healthy periapical tissues or to provide healing of them in restorable teeth, which have sufficient periodontal support. The amount of microbial cells in the root canal system and their virulence as well as host responses influence on the degree of periapical inflammation and symptoms. Microbial biofilm formation is typically seen on root canal walls but som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 42 publications
2
47
0
8
Order By: Relevance
“…[ 1 ] It has been shown that endodontic lesions do not develop in the absence of bacteria. [ 2 ] Primary infections of the endodontic space are mainly caused by obligate anaerobic species,[ 3 ] while the most responsible one for endodontic failure is Enterococcus faecalis . [ 4 ] This bacterium is able to withstand many intracanal medications[ 5 6 7 ] and also represents an important microorganism in the biofilm development, even though some articles suggest that calcium hydroxide is able to kill it.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] It has been shown that endodontic lesions do not develop in the absence of bacteria. [ 2 ] Primary infections of the endodontic space are mainly caused by obligate anaerobic species,[ 3 ] while the most responsible one for endodontic failure is Enterococcus faecalis . [ 4 ] This bacterium is able to withstand many intracanal medications[ 5 6 7 ] and also represents an important microorganism in the biofilm development, even though some articles suggest that calcium hydroxide is able to kill it.…”
Section: Introductionmentioning
confidence: 99%
“…As root canals are colonized and invaded by C. albicans [3,21], it encounters host cells and elicits an immune response from periapical tissues. Histopathologically, chronic apical periodontitis lesions involve periapical granulomas and sometimes apical cysts.…”
Section: Virulence Factors and The Pathogenetic Mechanism In Pulp Andmentioning
confidence: 99%
“…Somewhere between 300 and 700 bacterial species can be found in the oral cavity, with any particular individual harboring 100–200 of these species (Table 5) [80,81,82,83,84,85,86,87,88,89,90,91].…”
Section: Contemporary Perspectivesmentioning
confidence: 99%